Rapid orbital expansion in millisecond pulsar PSR J0636+5128: evaporation winds?. Issue 2 (28th November 2020) - Chen, Wen-Cong
ABSTRACT: PSR J0636+5128 is a 2.87 ms binary millisecond pulsar (MSP) discovered by the Green Bank Northern Celestial Cap Pulsar Survey, and possesses the third shortest orbital period ( P = 1.6 h) among confirmed binary pulsars. Recent observations reported that this source is experiencing a rapid orbital expansion at a rate of $\dot{P}=(1.89± 0.05)× 10^{-12}\, \rm s\, s^{-1}$ . The evaporation winds of the companion induced by the spin-down luminosity of the MSP may be responsible for such a positive orbital period derivative. However, our calculations show that the winds ejecting from the vicinity of the companion or the inner Lagrangian point cannot account for the observation due to an implausible evaporation efficiency. Assuming that the evaporation winds eject from the vicinity of the MSP in the form of asymmetric disc winds or outflows, the evaporation efficiency can be constrained to be ∼0.1. Therefore, the rapid orbital expansion detected in PSR J0636+5128 provides evidence of outflows and accretion disc around the MSP.